Answers

2016-03-26T14:46:57+08:00
Let  x   =   first odd number,  thus the second consecutive odd #  =  x + 2
      3 times first #  =    3 x
      5 more than twice the second #   =   2(x+2) + 5
       therefore             3 x =   2(x+ 2) + 5
                                    3 x       =  2 x + 9
                                       x    = 9
                   the second odd #  =   x + 2  =   9 + 2
                                                                  =   11
             the two consecutive odd number are    9 &11
0